Hypophysectomy, pituitary neuroadenolysis and pituitary radiosurgery for the treatment of refractory cancer pain: a historical review and mechanism investigation - Hu, Yuchen; Zhang, Wanghao; Chen, Zijian; Wu, Xiaoyan; Xue, Shuaishuai; Mao, Yangqi; Yi, Peiyao; Wei, Jiezuo; Qian, Dadi; Wang, Xingqin; Zhang, Peidong; Long, Hao (Frontiers in Neurology, 2025)
Refractory cancer pain affects 10–20% of patients with advanced malignancies and is not adequately controlled by opioids. The intrathecal therapy is an effective interventional procedure for referral, but the implanted infusion pumps are costly and the refilling requires technical expertise. Hypophysectomy, in its three stages—surgical, chemical, and radiosurgical—has emerged as an alternative for managing this pain. However, the underlying mechanism remains elusive, with existing hypotheses unable to comprehensively account for both the initial and long-term analgesic effects. This literature review explores the historical evolution, clinical outcomes, and hypothesized mechanisms of hypophysectomy for pain relief. Surgical hypophysectomy initially demonstrated an 85.5% success rate but carried significant risks like diabetes insipidus and hypopituitarism. Chemical hypophysectomy reduced invasiveness, achieving 75.1% pain relief with fewer complications. Modern pituitary radiosurgery has improved safety while maintaining high efficacy (initial relief: 95.9%, long-term: 73.5%). The mechanisms underlying pain relief remain unclear but include tumor regression, increased β-endorphins, neuroendocrine modulation, and hypothalamic involvement. A new hypothesis suggests that radiosurgery induces hormone redistribution (e.g., oxytocin, vasopressin) through hypothalamic–pituitary modulation, contributing to both immediate and long-term analgesia. Despite its potential, unresolved issues such as optimal radiation dose, pain assessment standardization, and precise mechanisms limit widespread adoption. This review underscores the need for larger, homogenous studies to validate the safety and efficacy of hypophysectomy in treating refractory cancer pain. These findings offer a promising avenue for improving palliative care in oncology.